Genotype-Related Effect of Crowding Stress on Blood Pressure and Vascular Function in Young Female Rats. (5th March 2014) - Slezak, Peter; Puzserova, Angelika; Balis, Peter; Sestakova, Natalia; Majzunova, Miroslava; Dovinova, Ima; Kluknavsky, Michal; Bernatova, Iveta
Abstract : This study investigated the influence of chronic crowding stress on nitric oxide (NO) production, vascular function and oxidative status in young Wistar-Kyoto (WKY), borderline hypertensive (BHR) and spontaneously hypertensive (SHR) female rats. Five-week old rats were exposed to crowding for two weeks. Crowding elevated plasma corticosterone ( P < 0.05 ) and accelerated BP (P < 0.01 versus basal) only in BHR. NO production and superoxide concentration were significantly higher in the aortas of control BHR and SHR versus WKY. Total acetylcholine (ACh)-induced relaxation in the femoral artery was reduced in control SHR versus WKY and BHR, and stress did not affect it significantly in any genotype. The attenuation of ACh-induced relaxation in SHR versus WKY was associated with reduction of its NO-independent component. Crowding elevated NO production in all strains investigated but superoxide concentration was increased only in WKY, which resulted in reduced NO-dependent relaxation in WKY. In crowded BHR and SHR, superoxide concentration was either unchanged or reduced, respectively, but NO-dependent relaxation was unchanged in both BHR and SHR versus their respective control group. This study points to genotype-related differences in stress vulnerability in young female rats. The most pronounced negative influence of stress was observed in BHR despite preserved endothelial function.